Data to improve air quality environmental justice outcomes in South Chicago - Illgner, Tara; Lad, Nikita (Frontiers in Public Health, 2022)
This brief provides data for policy changes on the intersection of polluting industrial facilities, marginalized communities, and the dearth of air-quality monitors in those communities of South Chicago. The allocation of air-quality monitors is determined by the Illinois Environmental Protection Agency (IEPA). Our data demonstrate that the air quality and subsequent health of Chicago's marginalized communities are chronically threatened by the expansion of polluting industries coupled with inadequate air-quality monitoring. The methods of data analysis presented here can be similarly applied to analyze air-quality disparities in communities beyond Chicago, including those that have been victims of environmental injustice stemming from redlining. Such data can be used to support Environmental Justice (EJ) advocacy and goals by informing remedial actions and policies of regulatory bodies, such as the IEPA, to reduce disproportionate air-quality burdens through increased monitoring. The generated maps may be used to direct plans for assessing and mitigating the effects of air pollution on human health.